Clinical features of adult patients with a definite diagnosis of central nervous system tuberculosis in an endemic country: A 13-year retrospective review - Suppachok Kirdlarp (2020)
© 2020 The Authors Rationale: Clinical features of central nervous system tuberculosis (CNS-TB) are nonspecific. The decision for treatment of the disease in an endemic area is challenging. Objectives: We aimed to study predictive factors for a definite diagnosis and outcome of patients with CNS-TB. Methods: A case-control study was performed in adults with a provisional diagnosis of CNS-TB in Thailand to determine predictive factors for a definite diagnosis of CNS-TB. Predictive factors for a definite diagnosis of CNS-TB were analyzed by multivariable logistic regression analysis. Factors associated with two-year mortality after the diagnosis of definite CNS-TB were determined using a cox regression analysis. Measurements and main results: A total of 114 patients received a provisional diagnosis of CNS-TB during the study period. A median (interquartile range) age was 40.8 (31.7–55.4) years, and 75 patients (65.8%) were male. Of these, 66 cases (57.9%) had definite CNS-TB, and 43 cases (38.4%) had HIV coinfection. By logistic regression, age, confusion, and nausea/vomiting were associated with definite CNS-TB (odds ratio [OR] 0.96, 95% confidence interval [CI] 0.93–0.99; p = 0.015, OR 2.86, 95% CI 1.03–7.94; p = 0.044, and OR 0.30, 95% CI 0.11–0.82; p = 0.019, respectively). In patients with definite CNS-TB, age and HIV coinfection were associated with two-year mortality (hazard ratio [HR] 1.07, 95% CI 1.01–1.13; p = 0.022, and HR 11.81, 95% CI 2.09–66.78; p = 0.005, respectively). Conclusions: Younger age, confusion, and absence of nausea/vomiting are predictive factors of a definite diagnosis of CNS-TB. In patients with definite CNS-TB, older age and HIV coinfection are associated with higher mortality. The results of this study might be helpful for the management of suspected CNS-TB cases as well as predicting the prognosis of CNS-TB cases in an endemic area.